2017
DOI: 10.2298/psi160921007s
|View full text |Cite
|
Sign up to set email alerts
|

Verbal aspect in Serbian children’s language production

Abstract: Previous studies have shown that an early usage of verbal aspect in children's spontaneous production is regularly observed in Slavic languages. However, this leads to the question whether the bare presence of aspect in early utterances is firm evidence that a child has acquired it. In order to show that the acquisition of aspect in Serbian is a process that lasts for several years, elicited production was inspected in children that had already achieved an apparent progress in language (3-5 year-olds). The com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
2
1
0
Order By: Relevance
“…A girl of 6;8 with the former diagnosis of articulatory difficulties used the verb 'live' when setting the scene of the story 'Dog' (6), and the verb 'love' when talking about the boy who lost his ball in the telling mode of the story 'Cat' (7). Our participants' generally competent use of tense and aspect marking is in line with the findings reported in Savić et al (2017) for Serbian, as well as the findings reported for other Slavic languages (e.g. Gagarina, 2004).…”
Section: Piloting Of Serbian Main: Preliminary Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…A girl of 6;8 with the former diagnosis of articulatory difficulties used the verb 'live' when setting the scene of the story 'Dog' (6), and the verb 'love' when talking about the boy who lost his ball in the telling mode of the story 'Cat' (7). Our participants' generally competent use of tense and aspect marking is in line with the findings reported in Savić et al (2017) for Serbian, as well as the findings reported for other Slavic languages (e.g. Gagarina, 2004).…”
Section: Piloting Of Serbian Main: Preliminary Resultssupporting
confidence: 91%
“…While the above studies (all published in Serbian) focused primarily on atypically developing children, a recent study published in English used the method of narrative elicitation to investigate the acquisition of aspectual distinctions in Serbian TD children (Savić, Popović & Anđelković, 2017). The ability to correctly mark temporal relations, as encoded by tense and aspect, is crucial in producing successful narratives.…”
Section: Background: Instruments Eliciting Narratives In Serbianmentioning
confidence: 99%
“…pas je bio srećan zato što je dog aux was happy because comp aux jeo kobasice eat-IPFV-SG-MASC sausages 'The dog was happy because he ate the sausages.' Our participants' generally competent use of tense and aspect marking is in line with the findings reported in Savić et al (2017) for Serbian, as well as the findings reported for other Slavic languages (e.g. Gagarina, 2004).…”
Section: (6)supporting
confidence: 91%